Arctic Militarisation and the Impact on Sustainable Development - Jenkins, Jamie (Helsingin yliopisto, 2020)
The Arctic environment is unique and hosts many economic opportunities. The environment is fragile and is home to many different animals, plants and indigenous people. The area has undergone periods of remilitarisation since the end of the cold war, and this is impacting local communities economically, environmentally and their social development. This research has been undertaken to assess the impact that military activity is having on these local communities. A literature review was undertaken in 3 key areas: Arctic sustainability, military sustainability and Arctic militarisation to identify relevant indicators that impact sustainable development. Sustainable development was defined using the 3 pillars from the Brundtland report, as economic, environmental and social. These indicators were collated to create a conceptual framework that was used to analyse two case study cities in the Arctic. These two cities were Fairbanks, in Alaska, and Severomorsk in Russia. These were chosen as economically and socially, they are very different, but they share the main similarity of being militarised Arctic cities. This meant the framework was tested on two different cities and in two different environments to test the validity and usefulness. The two case studies were built from reports, census information, statistical information and government reports. Although quantification was outside the scope of this research, observations were found from the data. Economically, the impact is positive. Military activity generates jobs, growth, infrastructure and military spending. The environmental impact is clearly negative. Military activity contaminates groundwater, soil, water and the local environment. The social impact is more ambiguous. Military activity helps foster community development but can impact personnel health. A discussion was undertaken on the effectiveness of the framework and improvement areas. The framework provided a good overall picture of activity but could be improved in some areas. These areas include ...